Marketing Analysis of Corn (Zea Mays) in Balai Kasih Village Kuala District Langkat Regency - Sinaga, Hardiansyah; Tifani, Puput; Mardhiyah, Ainul (ITScience (Information Technology and Science), 2024)
This research aims to 1). Knowing corn marketing channels in the research area. 2). Find out the cost of marketing corn in the research area. 3). Knowing the size of the corn marketing channel margin share in the research area. 4). To determine whether corn marketing in the research area is efficient. The location of this research is Balai Kasih Village, Kuala District, Langkat Regency. This research was carried out from August to September 2023. This type of research is quantitative and was carried out using interviews and questionnaires. The samples used in this research were 23 corn farmers and 3 traders, and the sampling method used was simple random sampling. The analysis methods used are marketing cost analysis, marketing margin and share margin, and marketing channel efficiency. The results of this research are: 1). There is 1 marketing channel pattern of farmer-trader collector-consumer with a total of 3 traders. 2). Marketing costs for collecting traders I are IDR 1,241/Kg, marketing costs for traders II are IDR 1,077/Kg, and marketing costs for traders III are IDR 676/Kg. 3). The share margin of collecting Trader I is 70%, the share margin value of Trader II is 71%, and the share margin of Trader III is 72%. 4). The marketing efficiency value of collecting Traders I is 21%, collecting Traders II is 18% and collecting Traders III has an efficiency value of 11%. All three are smaller than 50%, so they are considered efficient.